2009
DOI: 10.1111/j.1469-0691.2008.02097.x
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal mechanisms of aminoglycoside resistance in Pseudomonas aeruginosa isolates from cystic fibrosis patients

Abstract: In total, 40 Pseudomonas aeruginosa isolates from cystic fibrosis (CF) patients were included in this study. Twenty of these were collected in 1994 and 1997, from six CF patients, and the rest were collected from different CF patients in 2000 and 2001. The relative expression of mRNA for the efflux pump protein MexY was determined by real-time PCR and correlated with susceptibilities to amikacin and tobramycin. The chromosomal genes mexZ, rplY, galU, PA5471 and nuoG, which were found to have a role in the grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
53
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 25 publications
5
53
1
Order By: Relevance
“…Contrary to what we observed in the acrB mutant, Pérez et al showed modest decreases in the MICs of aminoglycosides in the acrA mutant of E. cloacae (27). It has been reported that the overexpression of MexY correlated with decreased susceptibility to aminoglycosides of P. aeruginosa and that the RND protein AdeB of Acinetobacter baumannii was responsible for aminoglycoside resistance (40,41). Interestingly, ECL_01758 was found to be the polypeptide most homologous to AdeB (58% identity and 76% similarity).…”
Section: Resultscontrasting
confidence: 49%
“…Contrary to what we observed in the acrB mutant, Pérez et al showed modest decreases in the MICs of aminoglycosides in the acrA mutant of E. cloacae (27). It has been reported that the overexpression of MexY correlated with decreased susceptibility to aminoglycosides of P. aeruginosa and that the RND protein AdeB of Acinetobacter baumannii was responsible for aminoglycoside resistance (40,41). Interestingly, ECL_01758 was found to be the polypeptide most homologous to AdeB (58% identity and 76% similarity).…”
Section: Resultscontrasting
confidence: 49%
“…However, the ⌬mexXY strain actually grows slightly faster than the parent isolate ( Table 1). The MexXYOprM pump is especially effective in extruding aminoglycosides (27), and the 96-month isolate is resistant to tobramycin, with a MIC 32 times higher than that of the parent strain ( Table 1). The parent strain was rapidly killed by tobramycin at the stationary phase, with little evidence for surviving persisters (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For aminoglycosides, the higher potency of tobramycin over amikacin in our collection also reflects what is observed in MIC distributions of wild-type strains assembled by EUCAST (29). Tobramycin has been described as a poorer substrate than amikacin for the efflux pump MexXY-OprM, considered responsible for natural and adaptive resistance to aminoglycosides in P. aeruginosa (36,37).…”
Section: Discussionmentioning
confidence: 99%